Artaud and His Doubles - Jannarone, Kimberly (Theater--theory/text/performance., 2010)
This is an unlooked-for project. Like many others, I first saw Artaud through the filters of American experimental theater and post-structuralism. My earliest work on Artaud began from accepted familiar premises, largely established in the 1960s: Artaud as prophet, madman, genius, was the thing to study; his significance lay in his status as an inspirational figure manifesting a largely ahistorical impulse; his denunciation of civilization's discontents implied a progressive critique. My research led me in different directions, however. Fueled by a desire to really read Artaud's works closely especially his early writing and his productions--I dug into the archives to research Artaud's theatrical practice.